2019
DOI: 10.2196/10658
|View full text |Cite
|
Sign up to set email alerts
|

Use of Physical Activity Monitoring Devices by Families in Rural Communities: Qualitative Approach

Abstract: Background Several studies support the impact of information communication technology–based interventions to promote physical activity among youth. However, little is known on how technology can be used by the entire family to encourage healthy behavior. Previous studies showed that children and youth rely and are dependent upon the decisions and values of their caregivers when it comes to having a healthy lifestyle. Thus, the exploration of behavior and attitudes of the entire family is needed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Fifteen studies [32,33,49,50,57,58,[60][61][62][63]65,67,68,71,72] were included in the thematic synthesis. Eleven [33,49,57,58,[60][61][62][63]65,68,71] provided quotations from participants.…”
Section: Thematic Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies [32,33,49,50,57,58,[60][61][62][63]65,67,68,71,72] were included in the thematic synthesis. Eleven [33,49,57,58,[60][61][62][63]65,68,71] provided quotations from participants.…”
Section: Thematic Synthesismentioning
confidence: 99%
“…Fifteen studies [32,33,49,50,57,58,[60][61][62][63]65,67,68,71,72] were included in the thematic synthesis. Eleven [33,49,57,58,[60][61][62][63]65,68,71] provided quotations from participants. Table 4 provides an overview of the themes identified, along with findings and supporting quotations.…”
Section: Thematic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, there is little research investigating the use, acceptability, feasibility, and/or effectiveness of wearables within the family [ 13 ]. A recent systematic review [ 13 ] identified two intervention studies (targeting adolescents) [ 14 , 15 ] and one feasibility study [ 16 ] using wearables in a family setting [ 13 ]. There was no evidence that family-based wearable interventions were effective at increasing adolescent PA [ 14 , 15 ], but parents reported becoming more aware of their child’s PA levels and having more conversations about health as a result of the wearable [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review [ 13 ] identified two intervention studies (targeting adolescents) [ 14 , 15 ] and one feasibility study [ 16 ] using wearables in a family setting [ 13 ]. There was no evidence that family-based wearable interventions were effective at increasing adolescent PA [ 14 , 15 ], but parents reported becoming more aware of their child’s PA levels and having more conversations about health as a result of the wearable [ 16 ]. Since this systematic review, a multi-component intervention (Step It Up Family), which incorporates wearables (Garmin Vivofit 3 and Vivofit jr), increased MVPA in children (6 to 10 years) and their mothers and fathers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%